The Genetic Components of a Natural Color Palette: A Comprehensive List of Carotenoid Pathway Mutations in Plants - Gupta, Prateek; Hirschberg, Joseph (Frontiers in Plant Science, 2022)
Carotenoids comprise the most widely distributed natural pigments. In plants, they play indispensable roles in photosynthesis, furnish colors to flowers and fruit and serve as precursor molecules for the synthesis of apocarotenoids, including aroma and scent, phytohormones and other signaling molecules. Dietary carotenoids are vital to human health as a source of pro-vitamin A and antioxidants. Hence, the enormous interest in carotenoids of crop plants. Over the past three decades, the carotenoid biosynthesis pathway has been mainly deciphered due to the characterization of natural and induced mutations that impair this process. Over the year, numerous mutations have been studied in dozens of plant species. Their phenotypes have significantly expanded our understanding of the biochemical and molecular processes underlying carotenoid accumulation in crops. Several of them were employed in the breeding of crops with higher nutritional value. This compendium of all known random and targeted mutants available in the carotenoid metabolic pathway in plants provides a valuable resource for future research on carotenoid biosynthesis in plant species.